Systematic reviews in surgery: recommendations from the Study Center of the German Society of Surgery - Kalkum, Eva; Klotz, Rosa; Seide, Svenja; Hüttner, Felix; Kowalewski, Karl-Friedrich; Nickel, Felix; Khajeh, Elias; Knebel, Phillip; Diener, Markus K.; Probst, Pascal (Langenbeck's archives of surgery, 2021)
Background Systematic reviews are an important tool of evidence-based surgery. Surgical systematic reviews and trials, however, require a special methodological approach. - Purpose This article provides recommendations for conducting state-of-the-art systematic reviews in surgery with or without meta-analysis. - Conclusions For systematic reviews in surgery, MEDLINE (via PubMed), Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) should be searched. Critical appraisal is at the core of every surgical systematic review, with information on blinding, industry involvement, surgical experience, and standardisation of surgical technique holding special importance. Due to clinical heterogeneity among surgical trials, the random-effects model should be used as a default. In the experience of the Study Center of the German Society of Surgery, adherence to these recommendations yields high-quality surgical systematic reviews.
Gesehen am 11.09.2023